The effect of brief case management on emergency department use of frequent users in mental health: Findings of a randomized controlled trial. - Vicky Stergiopoulos; Agnes Gozdzik; Ashley Cohen; Tim Guimond; Stephen W Hwang; Paul Kurdyak; Molyn Leszcz; Donald Wasylenki (PLoS ONE, 2017)
Frequent users of hospital emergency departments (EDs) are a medically and socially vulnerable population. The Coordinated Access to Care from Hospital EDs (CATCH-ED) study examined the effectiveness of a brief case management intervention in reducing ED use and improving health outcomes among frequent ED users with mental health or addiction challenges in a large urban centre. Adults (≥18 years of age) who had five or more ED visits in the past 12-months, with at least one visit for mental health or addictions problems were randomized to either brief case management (N = 83) or usual care (N = 83) and followed for 12 months. The primary outcome of effectiveness was the frequency of ED visits during 12 months after study enrolment. Secondary outcomes included days in hospital, mental health and addiction symptom severity and health-related quality of life, measured by the SF-12. Compared to usual care, CATCH-ED participants saw a 14% reduction in frequency of ED visits during the 12-month post-randomization period [rate ratio (RR) = 0.86, 95% CI 0.64-1.15)], however, this finding did not reach statistical significance. There were also no statistically significant differences between the groups at 12 months in the number of days spent in hospital (RR = 1.16, 95% CI 0.59-2.29), physical (1.50, 95% CI -2.15-5.15) or mental (-3.97, 95% CI -8.13-0.19) component scores of the SF-12, severity of psychiatric symptoms (-0.41, 95% CI -2.30-1.49), alcohol (0.053 95% -0.017-0.12) or drug (-0.0027, 95% CI -0.0028-0.023) use. Compared to usual care, a brief case management intervention did not result in significantly reduced ED use or improved health outcomes among frequent ED users with mental health or addictions challenges in a large urban centre in Canada. Future studies need to evaluate the availability and accessibility of community-based resources for individuals with frequent ED use.